Social dynamics in natural populations of Pseudomonas aeruginosa - Ghoul, M (2014)
Microbes rely on collective behaviours, such as communication and cooperation to survive and form communities. The majority of these social behaviours are mediated by the secretion of public good molecules into a shared environment such that they can be utilized by neighbouring cells. Therefore, individuals that engage in costly cooperative behaviour are susceptible to exploitation by selfish cheats that gain the benefit of cooperation without investing their share of the public good cost. Understanding such bacterial social interactions and the underlying molecular mechanisms gives insight into their complex social life in natural environments and can be used to develop alternative treatments for pathogenic bacteria that rely on such social interactions for virulence and to infect hosts. In this thesis I examine social behaviours expressed by the opportunistic pathogen, Pseudomonas aeruginosa. I develop an understanding of bacterial social dynamics, particularly competitive dynamics between cooperator and cheat strains and strains that engage in bacteriocin-mediated chemical warfare. I investigate bacterial cheat-cooperator systems in several ways: 1) I begin with a review describing the evolution of and response to cheating across a range of organisms and discuss the confusion that arises in identifying cheats particularly in microbial studies and therefore propose a key to identify cheating behaviour. 2) I empirically test whether cheating behaviour is context dependent in bacterial populations and reveal that the ability to cheat varies with the abiotic and social environment, which are two fluctuating conditions in natural environments. 3) I take an experimental approach to investigate why cheat invasion is not commonly observed in natural bacterial populations by testing the effect of cooperative bacterial growth dynamics on cheating ability. I find that secretion of public goods varies with bacterial growth dynamics and physiological growth stages which may explain why cheat invasion is more commonly observed in lab cultures and not in established natural populations. 4) In the final chapter I experimentally use natural isolates to examine the role of bacteriocins in mediating competition in pathogenic populations and find that contrary to empirical and theoretical work, bacteriocins do not play a significant role in strain competitive success and dominance. The thesis has laid groundwork for studying and understanding the role of social behaviours in bacterial systems and for further exploring social dynamics in natural bacterial populations.